PENGARUH KUALITAS PRODUK, BRAND IMAGE, BRAND TRUST DAN PRICE TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis UNISMA Angkatan 2018) - Heni Lutfia Sari; Rois Arifin; Muhammad Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to determine the effect of product quality, brand image, brand trust and price on oppo smartphone purchasing decisions (case studies on students of the economic faculty and business unisma class of 2018). The variables used in this study are purchasing decision variables (dependent variable), while the independent variables are product quality, brand image, brand trust and price.The results of this study partially conclude that there are effects between product quality variables, brand image, brand trust and price on purchasing decisions and conclude conclusively that there is an influence between product quality variables, brand image, brand trust and price on purchasing decisions.Keywords purchasing decisions, product quality, brand image, brand trust, price.